Athermal stability, bleaching behavior and dose response of luminescence signals from almandine and kyanite - Del Río, I; Sawakuchi, A. O.; Giordano, D.; Mineli, T. D.; Nogueira, L.; Abede, T. (Ancient TL, 2019)
In order to evaluate the suitability of minerals other than quartz and feldspar for luminescence dating of sediments, luminescence properties from almandine and kyanite relevant for dosimetry such as luminescence signal stability, bleachability by sunlight exposure, and dose response are investigated. Thermoluminescence (TL) signals (UV emission) from almandine aliquots present athermal instability for the entire tested TL temperature range (25 – 450 °C). Almandine also presents a significant infrared stimulated luminescence (IRSL), post-infrared IRSL (post-IR IRSL) and optically stimulated luminescence (OSL) (blue stimulation and UV detection) signals. Kyanite aliquots show a TL glow curve (UV emission) characterized by four distinct peaks at temperatures of around 90, 170, 220 and 325 °C. The 325 °C TL peak seems to be stable, without significant decay after 6.8 hours of storage at room temperature (25 °C). Kyanite aliquots did not yield significant IRSL or post-IR IRSL signals, but OSL is observed in the UV detection window. Fading tests for the OSL signals resulted in g-values of 15.8 ± 2.8 %/decade for almandine and 21.2 ± 11.6 %/decade for kyanite. The OSL signals are bleachable by sunlight with 34% to 50% of signal remaining after 5 minutes of light exposure. Both minerals yielded dose recovery ratios close to unity (given dose of 100 Gy) and the dose response curves had a high D0 values of around 800 Gy.